Teenage mutant ninja turtles: reborn, volume 4 ebook Sow wind, reap storm. - Campbell, Sophie (Teenage Mutant Ninja Turtles (2011), 2022)
The Shredder returns and Mutant Town is in danger of being destabilized by forces outside and in! Oroku Saki has been to hell and back, but will he now come to the Turtles as friend or foe? Meanwhile, April makes a stand against Baxter Stockman—with dangerous consequences—and the Mutanimals take drastic steps that will put them on a collision course with the TMNT! Then, as a protest at the Mutanimals HQ turns violent, TMNT allies and enemies rush to take advantage of the situation, but not before Old Hob makes a surprise decision that will shake allegiances! Collects issues #118–123 of IDW's Teenage Mutant Ninja Turtles.